2019
DOI: 10.1159/000502203
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes and Pathways Associated with Acne Using Integrated Bioinformatics Methods

Abstract: Background: Acne is the most common skin inflammatory condition. The pathogenesis of acne is not fully understood. Aims: We performed weighted gene co-expression network analysis (WGCNA) to select acne-associated genes and pathways. Methods: GSE53795 and GSE6475 datasets including data from lesional and nonlesional skin of acne patients were downloaded from the NCBI Gene Expression Omnibus. Differentially expressed genes (DEGs) in lesions were identified following a false discovery rate <0.05 and | log2 fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…Through analyzing bacterial metabolic pathways, this approach led to a potential mechanism of supplemented VitB12-induced acne [121]. WGCNA was utilized to construct interaction networks which highlight the role of central cytokines in the disease's pathophysiology (e.g., IL1β and CXCl1/2) [122,123]. Recently, the role of miRNAs was also introduced into this research field as depicted in Table A2 [124,125].…”
Section: Other Inflammatory Skin Diseasesmentioning
confidence: 99%
“…Through analyzing bacterial metabolic pathways, this approach led to a potential mechanism of supplemented VitB12-induced acne [121]. WGCNA was utilized to construct interaction networks which highlight the role of central cytokines in the disease's pathophysiology (e.g., IL1β and CXCl1/2) [122,123]. Recently, the role of miRNAs was also introduced into this research field as depicted in Table A2 [124,125].…”
Section: Other Inflammatory Skin Diseasesmentioning
confidence: 99%
“…Several studies have previously explored biomarkers using a combination of WGCNA and DEG identification to ensure reliability. [30][31][32] Therefore, a similar integrated method of analysis was used in our study, and characteristic genes in the chronic ITP group were shown to be Figure 6. Sub-network of hub genes related to the disease phenotype of chronic ITP.…”
Section: Discussionmentioning
confidence: 97%
“…Detection of C. acnes induced inflammatory cytokines provides a validation on effective inhibition on C. acnes growth. CXCL1/keratinocyte-derived chemokine (KC), CXCL2/MIP2 and CXCL5-6/lipopolysaccharide-induced CXC chemokine (LIX) were regarded as functional homologues of IL-8, where CXCL1, CXCL2 and CXCL6 are identified as candidates associated with acne pathogenesis in humans [39,40]. Additionally, multiple studies in the mouse acne model showed a remarkable increase in the production of neutrophils, macrophages and MIP-2 upon C. acnes administration into mice [41][42][43].…”
Section: Discussionmentioning
confidence: 99%